Developing interactive questions to measure the higher-order thinking skills of senior high schools’ students - A. Afandi; Saleh Hidayat; Indawan Syahri (University of Muhammadiyah Malang, 2019)
The traditional assessments which only covered lower-order thinking skills are still commonly used by teachers in Palembang. Yet the 21st-Century education demands the empowerment of higher-order thinking skills (HOTS). The objective of this study was to find out the validity, practicality, and effectiveness of interactive questions in measuring students' HOTS. The research and development applied was 4-D model which included four stages (define, design, develop and disseminate). The study was conducted on the tenth graders of SMAN (Sekolah Menengah Atas Negeri-State Senior High School) 4 Palembang, and SMAN 9 Palembang, in the even semester of academic year 2018/2019. The instruments of data collection were validation sheets and interactive questions. The data analysis techniques used were Microsoft Excel 2010 and WINSTEPS version 3.73.0. In conclusion, the study showed that: 1) the expert validation results were very high category; 2) the instrument was considered as good by teacher responses; and 3) the interactive questions were effective in measuring students’ HOTS.